A Cross-sectional Study Exploring the Knowledge, Perceptions, and Factors Influencing Prescriptions of Vietnamese Physicians with regard to Generic Medicines - Quang Vo, Dr.Trung (Asian Journal of Pharmaceutics (AJP), 2018)
Context: In Vietnam, which is a developing country, generic medicines have been suggested as a solution that should serve to decrease treatment costs. Physicians play a key role in facilitating and enhancing patientsâ€™ use of generic medicines. Aims: The aim of this study was to assess the knowledge, perceptions, and factors influencing prescriptions of physicians in Vietnam to suggest policies for effectively enhancing the use of generic medicines. Subjects and Methods: This cross-sectional research study was conducted using a 27-item questionnaire between January 2017 and April 2017 in a number of Vietnamese hospitals and private clinics. The sample size as calculated by Raosoft website was 383. Statistical Analysis Used: The Chi-square, Kruskalâ€“Wallis, and Mannâ€“Whitney U-tests were manipulated to calculate the association between the study variables. Results: Of the 405 responses received, 390 were eligible for inclusion in the study, which led to a response rate of 84.78%. In terms of the scoring of the physiciansâ€™ knowledge, 141 physicians (37.2%) gave the right number of answers, which was fewer than two. The percentages of the various levels of agreement with the notion that â€œgeneric medicines can be interchanged with brand name medicinesâ€ were independent of the physiciansâ€™ knowledge (P < 0.001). The age variable was strongly associated with the level of the physiciansâ€™ consensus (Spearmanâ€™s rho = 0.986, P < 0.001). Conclusions: Some policies based on the analyzed perception results are therefore suggested to enhance the efficacy of generic medication use as well as the quality of local generic medicines.